x![log_{(x-2)^{2}}(9^{x}-3)\leq0 log_{(x-2)^{2}}(9^{x}-3)\leq0](https://tex.z-dn.net/?f=log_%7B%28x-2%29%5E%7B2%7D%7D%289%5E%7Bx%7D-3%29%5Cleq0)
ОДЗ :
0\\2)x\neq2\\ 3)x-2\neq +-1" alt="1)9^{x}-3>0\\2)x\neq2\\ 3)x-2\neq +-1" align="absmiddle" class="latex-formula">
Значит : x ∈ (1/2 ; 1)∪(1 , 2)∪(2 , 3)∪(3 ; + ∞)
Решение:
((x - 2)² - 1)(3²ˣ - 3 - 1) ≤ 0
(x - 2 - 1)(x - 2 + 1)(3²ˣ - 2²) ≤ 0
![(x-3)(x-1)(3^{2x}-3^{2log_{3}2})\leq0\\\\(x-3)(x-1)(2x-2log_{3}2)\leq0\\\\(x-3)(x-1)(x-log_{3}2)\leq0 (x-3)(x-1)(3^{2x}-3^{2log_{3}2})\leq0\\\\(x-3)(x-1)(2x-2log_{3}2)\leq0\\\\(x-3)(x-1)(x-log_{3}2)\leq0](https://tex.z-dn.net/?f=%28x-3%29%28x-1%29%283%5E%7B2x%7D-3%5E%7B2log_%7B3%7D2%7D%29%5Cleq0%5C%5C%5C%5C%28x-3%29%28x-1%29%282x-2log_%7B3%7D2%29%5Cleq0%5C%5C%5C%5C%28x-3%29%28x-1%29%28x-log_%7B3%7D2%29%5Cleq0)
- + - + -
₀________[log_₃2]_________₀_________₀______
1/2 1 3
x ∈ (1/2 ; log_₃2] ∪ (1 , 2) ∪ (2 ; 3)